Investigation of integrated time nanosecond pulse irreversible electroporation against spontaneous equine melanoma - Fesmire, Chris C.; Peal, Bridgette; Ruff, Jennifer; Moyer, Elizabeth; McParland, Thomas J.; Derks, Kobi; O’Neil, Erin; Emke, Carrie; Johnson, Brianna; Ghosh, Shatorupa; Petrella, Ross A.; DeWitt, Matthew R.; et al. (Frontiers in Veterinary Science, 2024)
Integrated time nanosecond pulse irreversible electroporation (INSPIRE) is a novel tumor ablation modality that employs high voltage, alternating polarity waveforms to induce cell death in a welldefined volume while sparing the underlying tissue. This study aimed to demonstrate the in vivo efficacy of INSPIRE against spontaneous melanoma in standing, awake horses. A custom applicator and a pulse generation system were utilized in a pilot study to treat horses presenting with spontaneous melanoma. INSPIRE treatments were administered to 32 tumors across 6 horses and an additional 13 tumors were followed to act as untreated controls. Tumors were tracked over a 43-85 day period following a single INSPIRE treatment. Pulse widths of 500ns and 2000ns with voltages between 1000V and 2000V were investigated to determine the effect of these variables on treatment outcomes. Treatments administered at the lowest voltage (1000V) reduced tumor volumes by 11 to 15%. Higher voltage (2000V) treatments reduced tumor volumes by 84 to 88% and eliminated 33% and 80% of tumors when 500ns and 2000ns pulses were administered, respectively. This pilot study suggests that INSPIRE may be a safe and effective treatment for cutaneous tumors, warranting future study.